Impacto económico de la modalidad de estudio híbrida “distancia-virtual semipresencial” en la carrera de Ingeniería Agrícola - Kuffó Cedeño, Gema Elizabeth (2023)
The purpose of this research was to analyze the economic impact of the hybrid-study modality "virtual-distance-blended" on the students of the Agricultural Engineering major at ESPAM MFL. To this end, different activities were carried out to achieve the specific objectives using bibliographic, field and descriptive research methods, as well as techniques such as survey, interview, and the main inductive, deductive, analytical and synthetic methods. Likewise, the contents related to the research problem were analyzed, in which, among the main results obtained, it was found that during the changes in study modalities caused by the COVID-19 pandemic, various impacts were generated, where students indicated that 42% had economic affectations, 26% academic ones; on the other hand, 59% of them indicated that it was difficult to find a job during the pandemic, which prompted 43% of those surveyed to indicate that they fully agree that it was difficult to acquire technological tools to access classes. For this reason, an action plan is proposed as an ideal action to minimize the economic impact and to solve the students’ problems emerged due to the modality’s changes occurred during the health emergency, finally it was concluded that according to the diagnoses, the need to acquire technological tools considerably affected the economy of the students.